Spanish seamen : inter-departmental correspondence - Carthy, A. E.
C01-0013-001 TRADES UNION CONGRESS. INTER-DEPARTMENTAL CORRESPONDENCE. From A.E. Carthy To Mr. H.V. Tewson Department International Date 4th June 1940 SUBJECT. SPANISH SEAMEN Nationality where known: Basque Galicien Spanish Men only: Barry 1 1 _ _ Belfast 17 12 4 - Birkenhead 17 13 3 1 Bristol 2 2 _ - Cardiff 7 4 - 3 Hull 4 4 - - London 3 2 - 1 Newcastle-on-Tyne 6 1 2 3 Plymouth 3 3 — — Southampton 1 1 - _ Sunderland 3 2 _ - West Hartlepool 12 4 8 - 49 17 8 76 Occupations (including alternatives): Captains, Officers, Engineers, Mates 35 Seamen, Firemen, Boatswains, Donkeymen, Cooks 36 Fishermen 5 possible job: 13 Agricultural work 9 Commercial or clerical experience 3 Carpenters 2 Chauffeur 1 Bricklayer 1 PLEASE NOTE: The Basques and Galicians on the attached list will almost certainly have farming experience. There are 66 of them, out of the total of 76 men here. 292C/946/1/13